Aplicação de corretivos de acidez do solo na implantação do sistema plantio direto - Deus, Angélica Cristina Fernandes [UNESP] (2014)
In the no - tillage system, soil acidity correction practice is restricted to limestone use and there is little information regarding the use of steel slag. The study aimed to evaluate the amendments in soil chemical attributes, yield and nutrient u ptake of common bean, soybean and black oat according to the application forms of slags, compared to limestone, in the implantation of no till system. The experiment was conducted under a Rhodic Hapludox for three years (2010 - 2013). The treatments consiste d of surface and incorporated application of seven soil acidity correctives: steel slag (SS), blast furnace slag (BFS), ladle furnace slag (LFS), stainless steel slag (“agrosilício”) (AG), wollastonite (W), lime (L) and calcined dolomite lime (CDL), plus o ne control without corrective application. Each material dose was calculated to raise the base saturation to 70%. In February 2011, the first cultivation of bean ( Phaseolus vulgaris ) occurred. Afterwards, the experiment was developed according to a success ion of cultures, that is, in winter black oats was sown ( Avena strigosa ) and in summer, soybean ( Glycine max ) was sown. Soil acidity correctives materials provided changes in soil chemical properties, increased Ca, Mg, P and values of sum of bases, base saturation and CEC. The ladle furnace slag (LFS), SS and AG can be applied in the no - tillage system with similar efficiency to limestone to neutralize soil acidity. Higher solubility of the silicate in regard to the carbonate neither become the steel slag more efficient than the limes not even correct soil acidity faster at the establishment of no - tillage system. The common bean yield increases by application of correctives in soil acidity, while, black oat yield shows low answer to the correctives material s applications. The agrosilicate (AG), SS, LFL, W, CDL and L increases similarly soy bean yield in the no - tillage system ...